(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of vaccination coverage against hepatitis B virus (HBV) in Health Care Workers (HCWs) in tertiary care hospitals and to identify the common barriers to vaccination. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the ten Tertiary Care Hospitals of Pakistan located in Rawalpindi, Islamabad and Peshawar from January 2018 to May 2018. Materials and Methods: HCWs were evaluated through a self-administered questionnaire which included questions about demographics, HBV vaccination status and reasons for incomplete vaccination. Categorical variables were shown in percentages and Chi square test was used to determine the determinants of vaccination. Results: Of the total 1130 participants, 693 (61.3%) were males and mean age of the study participants was 28.8± 6.69 SD years. Of the total, 590 (52.2%) were fully vaccinated, 188 (16.6%) partially vaccinated, 307 (27.2%) non-vaccinated while 45 (4%) could not recall their vaccination history. Negligence followed by lack of knowledge were reported as common barriers to vaccination. Statistically significant association among age (p=0.025), type of profession (p< 0.001), duration of employment (p=0.035) and hepatitis B vaccine coverage was observed. Conclusion: There was low hepatitis B vaccine coverage among HCWs. A free and mandatory immunization program should be offered to all HCWs to achieve 100% vaccination coverage and ensure their protection against HBV.